Temporary employees’ assessment of onboarding - Kupczyk, Teresa; Kubicka, Joanna (Wdrożenie do pracy w ocenie pracowników tymczasowych, 2018)
The main objective of the research was to determine how temporary employees perceive the process of their onboarding in the context of the efficient performance of their responsibilities. The analysis covered the information obtained by the employee during onboarding, such as the employer’s expectations concerning the position in question, organization of work, procedures and values applied at the company, as well as work evaluation terms. A quantitative research was held based on a questionnaire filled in by 286 respondents. The study revealed that temporary employees had a good opinion of the methods of onboarding. It turned out that the opinion on onboarding, especially with respect to work organization, worsened with age. The study also determined that with increasing level of education, employees’ opinion worsened with regard to the completeness of information provided during onboarding and concerning work evaluation methods and the values applied at the company
Management Sciences = Nauki o Zarządzaniu, 2018, vol. 23, no. 4; s. 35-41
Keywords: onboarding; temporary employee; temporary work; assessment